Spotlight on mavrilimumab for the treatment of rheumatoid arthritis: evidence to date - Crotti C; Raimondo MG; Becciolini A; Biggioggero M; Favalli EG (Dove Medical Press, 2017)
Chiara Crotti,1 Maria Gabriella Raimondo,1 Andrea Becciolini,2 Martina Biggioggero,1 Ennio Giulio Favalli2 1Department of Clinical Sciences and Health Community, University of Milan, Division of Rheumatology, Gaetano Pini Institute, 2Department of Rheumatology, Gaetano Pini Institute, Milan, Italy Abstract: The introduction of biological therapies into clinical practice has dramatically modified the natural history of chronic inflammatory diseases, such as rheumatoid arthritis (RA). RA is a systemic autoimmune disease that causes articular damage and has a great negative impact on patients’ quality of life. Despite the wide spectrum of available biological treatments, ~30% of RA patients are still unresponsive, resulting in high disability and increased morbidity and mortality. In the last few decades, the scientific knowledge on RA pathogenesis vastly improved, leading to the identification of new proinflammatory molecules as potential therapeutic targets. Several in vitro and in vivo studies showed that granulocyte-macrophage colony-stimulating factor (GM-CSF), known to be a hematopoietic factor, is also one of the proinflammatory cytokines involved in macrophage activation, crucial for the pathogenic network of RA. Mavrilimumab, a human monoclonal antibody targeting the subunit α of GM-CSF receptor, was recently developed as a competitive antagonist of GM-CSF pathway and successfully adopted in human trials for mild to moderate RA. Mavrilimumab phase I and phase II studies reported an overall good efficacy and safety profile of the drug, and these encouraging results promoted the initiation of worldwide phase III studies. In particular, 158-week results of phase II trials did not show long-term lung toxicity, addressing the major concern about this target of pulmonary alveolar proteinosis development. However, further clinical studies conducted in larger RA populations are needed to confirm these promising results. This review summarizes the biological role of GM-CSF in RA and the preclinical and clinical data on mavrilimumab and other monoclonal antibodies targeted on this pathway as an alternative therapeutic option in RA patients who are unresponsive to conventional biological drugs. Keywords: rheumatoid arthritis, GM-CSF, mavrilimumab, monoclonal antibody, biologic drugs